Traditional Fish Gangan: An Icon of Gastronomic Tourism from Belitung Island - Pratiwi, Yunisti (Gastronomy Tourism Journal, 2020)
This study aims to develop a gastronomic tourism object in Belitung Island which has been known by its marine tourism. Traditional food namely fish Gangan is the object that will be examined and promoted as an icon of gastronomic tourism from Belitung Island. The method applied in this study is descriptive qualitative approach with observation, interview, and documentation as the research instruments. Â By conducting this research, it is expected that the fish gagan may become a culinary tourism icon of Belitung island which can attracts touristsâ€™ interest to visit the place. So that this product will give additional value for Belitung island as an attractive and sustainable tourism place.